Open Access and Scopus: A New Approach to Scientific Visibility From the Standpoint of Access - Miguel, Sandra (2011)
The last few years have seen the emergence of several open access (OA) options in scholarly communication, which can be grouped broadly into two areas referred to as gold and green roads. Several recent studies have shown how large the extent of OA is, but there have been few studies showing the impact of OA in the visibility of journals covering all scientific fields and geographical regions. This research presents a series of informative analyses providing a broad overview of the degree of proliferation of OA journals in a data sample of about 17,000 active journals indexed in Scopus. This study shows a new approach to scientific visibility from a systematic combination of four databases: Scopus, the Directory of Open Access Journals, Rights Metadata for Open Archiving (RoMEO)/Securing a Hybrid Environment for Research Preservation and Access (SHERPA), and SciMago Journal Rank) and provides an overall, global view of journals according to their formal OA status. The results primarily relate to the number of journals, not to the number of documents published in these journals, and show that in all the disciplinary groups, the presence of green road journals widely surpasses the percentage of gold road publications. The peripheral and emerging regions have greater proportions of gold road journals. These journals belong for the most part to the last quartile. The benefits of OA on visibility of the journals are to be found on the green route, but paradoxically, this advantage is not lent by the OA, per se, but rather by the quality of the articles/journals themselves regardless of their mode of access